The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1039/c7mt00299h
|View full text |Cite
|
Sign up to set email alerts
|

A cytosolic copper storage protein provides a second level of copper tolerance inStreptomyces lividans

Abstract: Streptomyces lividans has a distinct dependence on the bioavailability of copper for its morphological development. A cytosolic copper resistance system is operative in S. lividans that serves to preclude deleterious copper levels. This system comprises of several CopZ-like copper chaperones and P-type ATPases, predominantly under the transcriptional control of a metalloregulator from the copper sensitive operon repressor (CsoR) family. In the present study, we discover a new layer of cytosolic copper resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(64 citation statements)
references
References 69 publications
4
60
0
Order By: Relevance
“…Growth of isolates at higher concentrations of various metal ions is due to a variety of reasons such as requirement of heavy metal ions for cell growth and metabolism; requirement of these metal ions as cofactors for various enzymes may be due to multi-dimensional heavy metal resistance mechanisms, and bioaccumulation or transformations of metal ions (Straw et al 2018). Zn 2+ and Cu…”
Section: Discussionmentioning
confidence: 99%
“…Growth of isolates at higher concentrations of various metal ions is due to a variety of reasons such as requirement of heavy metal ions for cell growth and metabolism; requirement of these metal ions as cofactors for various enzymes may be due to multi-dimensional heavy metal resistance mechanisms, and bioaccumulation or transformations of metal ions (Straw et al 2018). Zn 2+ and Cu…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, BsCsp3-bound Cu(I) can be withheld from the efflux pump. It has also been found that in S. lividans Csp3 enables growth at higher Cu levels (75).…”
Section: The Functions Of Cspsmentioning
confidence: 99%
“…S1 in ref. 75) are identical to bacterial Csp sequences and are therefore most likely not from the organism indicated, but are due to contamination with bacterial DNA. This is not surprising given that the bacteria in question are either soil dwelling or widely distributed in the environment.…”
Section: Csp Homologues In Non-methanotrophsmentioning
confidence: 99%
See 2 more Smart Citations